GLOB: A global project management readiness framework. Issue 12 (9th July 2020) - Niazi, Mahmood; Mahmood, Sajjad; Alshayeb, Mohammad
Abstract: In global software development (GSD), software is developed by a team of geographically dispersed people. Many organizations that develop projects globally do not evaluate their project management readiness to undertake such projects. The objective of this paper is to propose a global project management readiness framework (GLOB) to help organizations in evaluating and assessing their GSD project management readiness to improve their capabilities in managing GSD projects. To develop GLOB, three systematic literature reviews (SLRs) were conducted. For each SLR, an empirical study was conducted with GSD practitioners to validate the SLR results in a real‐world environment. We identified 45 factors that can play a positive or negative role in global project management readiness. In total, 305 best practices were identified for global project management. Based on the findings of the SLRs and empirical studies, GLOB was developed. Two case studies were conducted to evaluate GLOB in a real‐world context. The case study results show that GLOB has the potential to measure an organization's project management readiness for global projects. It is hoped that GLOB will provide GSD practitioners with the ability to understand the strengths and weaknesses of current project management processes and to address weak areas.